2021
DOI: 10.1109/access.2021.3058120
|View full text |Cite
|
Sign up to set email alerts
|

Four-Directional Total Variation With Overlapping Group Sparsity for Image Denosing

Abstract: In this paper, a new model combining four-directional total variation with overlapping group sparsity is proposed, which not only suppresses the staircase effects introduced by traditional total variation, but also fully utilizes the gradient neighborhood information on each pixel of the image. In order to decrease the computation time of image denoising, the alternating direction method of multipliers (ADMM) is adopted to divide the complex optimization problem into separate subproblems that are easy to solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…The impact of single direction constraint over a limited angle tomographic image taken from both x and y directions also showed that the directional information plays an important role in feature preservation in the image taken from a limited view angle ( Zhang et al, 2021 ). There have been alternative modified gradient based total variation algorithms ( Zhang et al, 2021 ; Sakurai et al, 2011 ; Fan Liao & Shu, 2015 ; Huang et al, 2016 ; Huang et al, 2018 ; Hu & Jacob, 2012 ; Zhou & Fan, 2021 ). Sakurai et al proposed a faster four directional TV algorithm that brings two additional partial terms to the horizontal and vertical directional terms in classical TV ( Sakurai et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of single direction constraint over a limited angle tomographic image taken from both x and y directions also showed that the directional information plays an important role in feature preservation in the image taken from a limited view angle ( Zhang et al, 2021 ). There have been alternative modified gradient based total variation algorithms ( Zhang et al, 2021 ; Sakurai et al, 2011 ; Fan Liao & Shu, 2015 ; Huang et al, 2016 ; Huang et al, 2018 ; Hu & Jacob, 2012 ; Zhou & Fan, 2021 ). Sakurai et al proposed a faster four directional TV algorithm that brings two additional partial terms to the horizontal and vertical directional terms in classical TV ( Sakurai et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%